2008
DOI: 10.1097/lgt.0b013e31815d8d88
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Among Immigrants and Ethnic Minorities

Abstract: Health care providers and policy makers must be cognizant of the various sociocultural factors influencing health-related beliefs and health care utilization among immigrant and ethnic minorities in the United States. Culturally relevant screening strategies and programs that address these sociocultural factors must be developed to address the growing disparity in cervical cancer burden among underserved, resource-poor populations in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
196
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(210 citation statements)
references
References 54 publications
12
196
0
2
Order By: Relevance
“…Not go to the doctors for control unless people do not feel fine, negatively affect the early diagnosis. The same idea has been expressed in other studies (Boyer et al, 2001;Wackerbarth et al, 2005, Johnson et al, 2008.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Not go to the doctors for control unless people do not feel fine, negatively affect the early diagnosis. The same idea has been expressed in other studies (Boyer et al, 2001;Wackerbarth et al, 2005, Johnson et al, 2008.…”
Section: Discussionsupporting
confidence: 60%
“…In our study, it is glad to see that the rate of people with the thought of taking physical examination and tests are not a sin is quite high for a country like Turkey, which is an Islamic one. Other studies found that women preferred to be examined by female doctors (Boyer et al, 2001;Austin et al, 2002;Wackerbarth et al, 2005;Johnson et al, 2008). The half of the people stated that cancer is a case that comes from Allah.…”
Section: Discussionmentioning
confidence: 99%
“…The participation in screening programs 11 may have a strong cultural component, as has been shown by other studies in other contexts. 6,10 This investigation presents certain limitations. An absence of variables related to the migratory process, including duration of residence in Spain or native language, has already been mentioned.…”
Section: Discussionmentioning
confidence: 95%
“…There have been studies exploring patient barriers to cervical cancer screening [11][12][13][14][15] , attitudes and beliefs about human papilloma virus (HPV) and the HPV vaccine [16][17][18] ; however, few have focused on barriers to follow-up of an abnormal Pap smear 3,6,7,16 . Del Carmen and colleagues explored sociodemographic and knowledge differences between Latina and non-Latina women referred to colposcopy 7 .…”
Section: Introductionmentioning
confidence: 99%